E-counselling process and skills: a literature review - Asri, Alia Sarah; Zainudin, Zaida Nor; Wan Othman, Wan Norhayati; Hassan, Siti Aishah; Ahmad, Nor Aniza; Abu Talib, Mansor; Mohamad Yusop, Yusni (Innovare Academics Sciences, 2020)
The world in 21st century now is moving and developing at a fast rate which influences growth in variety of fields including the counselling field. As individuals are becoming more tech-savvy, and geographical distance no longer considered as an obstacle, counselling over the virtual environment is becoming a possible modality and alternative to traditional or face-to-face counselling. Although there are currently many counsellors who are offering online services, there is, however, a lack of reference or structure on how they are conducting the sessions ethically and effectively. Hence, this review paper serves to address the lack of studies conducted on the e-counselling practice guidelines, while identifying counselling process and skills that are used by online counsellors. This systematic literature review applied PRISMA method where Inclusion and Exclusion criteria process are applied.. The articles are retrieved from two databases, Scopus and Academic Search Complete, where finally a total 25 articles were identified and reviewed. The findings from this study showed that there are many counselling skills and counselling process used in face-to-face counselling which are incorporated into online setting, along with addition of other skills, techniques and process which are prevalent in distant communication. The findings and data found from this study are expected to be fully utilized by online practitioners and counsellors most particularly, and as a reference for other researchers to improve and conduct more thorough studies on counselling delivery and modalities.